Kualitas Pelayanan PT. Pertamina (Persero) Dalam Penyaluran Bahan Bakar Minyak (BBM) di Kabupaten Merauke - Irawan, Andri (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2019)
The realization of quality public services is one of the characteristics of good governance as a goal of the utilization of the state apparatus. Therefore, every public and private organization is demanded to be able to provide quality services. This study aims to describe and analyze the quality of service of PT. Pertamina (Persero) in distributing fuel oil (BBM) in Merauke Regency with a qualitative approach. The results showed that the quality of fuel distribution services conducted by PT Pertamina of Merauke Regency has not fully met the criteria of quality service. This can be seen from the service quality indicators that are related to responsiveness and reliability. Where in this reliability and responsiveness service shows the time of service hours at Pertamina, some partners are still not satisfied with the timely service hours because there are still many factors that influence it, the ability of the apparatus, service system and service facilities which still do not provide the system services that do not meet the service quality standards at Pertamina are on time, on the right amount, on the right quality.